(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To say that Rabindranath Tagore was a prolific dramatist would be an understatement. In his sixty-year career as a playwright, he wrote more than fifty works in the dramatic mode. He tried his hand at so many different styles that a classification of his dramatic output is essential. Tagore himself applied the following terms to his plays ntak or ntya (drama), ntyakvya (dramatic poem), ntik (playlet), prahasan (farce), gitintya (musical drama), and nritya-ntya (dance drama). His conventional ntya can be further subdivided into two categories—the early blank-verse dramas The King and the Queen and Sacrifice and the others, numbering twenty, all written in prose and, with one exception, published after 1907. Although Tagore separately classified seven of his works as “dramatic poems,” they are technically similar to the two verse ntya, the only substantial difference being that the latter are in five acts. Because all seven “dramatic poems” were printed by 1900, it would be appropriate to categorize them chronologically, together with the two poetic plays, as his early dramatic work in verse. To them should be added two of Tagore’s “playlets,” both written in verse, published during this same period.